The Impact of Illegal Mine C Mining and Regulatory Reform in East Kalimantan - Fitriani, Nur Annisa; Ahya, Urfan; Masjaya, Masjaya; Effendi, Safaranita Nur (HK-Publishing, 2024)
AbstractMining activities are activities that utilize natural resources that have a direct impact on the environment. Development activities that do not comply with regulations and are not sustainable have the potential to cause major damage to the environment. C Excavation Mining is a type of mining whose scope is smaller than mineral and coal mining. However, because its scope is smaller, this does not mean that Excavation C mining does not have an impact on the environment. As a region rich in natural resources, East Kalimantan is a province with enormous potential in the mining sector. With this great potential, regulations are important to regulate all types of mining operations. In 2022, authority over mining permits, which was previously in the hands of the center, will again be in the hands of regional governments. However, East Kalimantan in particular still does not have a PERGUB regulation regarding the Galian C mine, so there are several cases involving the illegal Galian C mine and its negative impact on the related environment. This article will briefly discuss how the absence of a PERGUB regulating the illegal mining of Excavation C has resulted in losses and hampered East Kalimantan's natural resource wealth, and what recommendations for regulatory reform the local government can carry out regarding this issue.Keywords: Galian C, Governor Regulation, East Kalimantan